2014
DOI: 10.1016/j.ijid.2013.12.011
|View full text |Cite
|
Sign up to set email alerts
|

Long-term outcomes of HIV-infected children in Thailand: the Thailand Pediatric HIV Observational Database

Abstract: Although most children initiated ART at low CD4 levels, the majority achieved immune reconstitution and long-term virological control. Earlier treatment may improve these outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
11
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 12 publications
(26 reference statements)
6
11
1
Order By: Relevance
“…In our cohort, the cumulative probability of death was estimated to be 5.3% at 1 year after enrolment; similarly, the 12-month mortality rate was 6.6 deaths per 100 PYs of follow-up. These results are similar to other large pediatric cohort studies in SubSaharan Africa [19–24], but higher than rates found in mature Asian pediatric ART cohorts [25, 26]. A review by Peacock-Villada et al [27] synthesizing and comparing clinical outcomes from published studies of pediatric ART programs in resource-limited versus developed countries found a similar overall mean mortality of 7.6% among 30 cohorts from resource-limited countries, and 7.4% among African cohorts specifically, with most cohorts reporting on approximately 12 months of follow up time.…”
Section: Discussionsupporting
confidence: 91%
“…In our cohort, the cumulative probability of death was estimated to be 5.3% at 1 year after enrolment; similarly, the 12-month mortality rate was 6.6 deaths per 100 PYs of follow-up. These results are similar to other large pediatric cohort studies in SubSaharan Africa [19–24], but higher than rates found in mature Asian pediatric ART cohorts [25, 26]. A review by Peacock-Villada et al [27] synthesizing and comparing clinical outcomes from published studies of pediatric ART programs in resource-limited versus developed countries found a similar overall mean mortality of 7.6% among 30 cohorts from resource-limited countries, and 7.4% among African cohorts specifically, with most cohorts reporting on approximately 12 months of follow up time.…”
Section: Discussionsupporting
confidence: 91%
“…Despite late start of treatment, 2‐year mortality rates (5.1 per 100 person‐years) were good and similar to estimates reported in other sub‐Saharan African and South‐East Asian programmes . Lower death rates have been reported in Thailand (1.3 deaths/100 person‐years) , and higher estimates in rural Mozambique, where 39% LTFU and 29% death after 2 years on ART were reported among 735 children . Comparisons of mortality across settings are, however, problematic, due to disparities in undocumented deaths.…”
Section: Discussionsupporting
confidence: 68%
“…Indeed, better survival in children with greater adherence to placebo in co-trimoxazole prophylaxis trial suggests that good adherence may be a surrogate for overall better child care [37]. Mortality at ≥2 years on cART from routine programs in RLS ranges from 3.7 to 29% [38,39] and rates vary from 1.3–6.0/100 CY [40,41]. Children still initiate treatment with severe disease with mortality remaining higher in the first year (Figure 3)[42].…”
Section: Survival On Cart In Routine Carementioning
confidence: 99%